The evolution of the spatial pattern of white residential development and the housing market in Johannesburg - Hart, Graeme Hilton Thurlow (My University, 2015)
The problem of residential development and the price of residential property is investigated through an empirical study of the city of Johannesburg from its inception in 1886 to 1972. The analysis is temporal and spatial and is based upon municipal valuations and sales data of residential property. The analytic framework is developed from urban growth theory on the one hand, and the theory of the urban land market, on the other. The findings reveal that both residential development and residential property prices are dependent upon a wide variety of socially rooted and economically rooted determinants and that these act in concert to produce the dynamic spatial pattern found in the urban system.
A thesis submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg for the degree of Doctor of Philosophy Johannesburg, 1974